2015
DOI: 10.4103/0970-9290.159169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of highly active antiretroviral therapy use on oral manifestations in pediatric patients infected with HIV

Abstract: Although the prevalence of oral lesions was similar between the groups, it was less in patients without AIDS and those under HAART. The duration of HAART usage had a significant influence on the prevalence of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 1 publication
0
14
0
2
Order By: Relevance
“…Additionally, Oliscovicz et al (2015) showed that 65.8% of the HIV-positive children that were included in the study had already developed AIDS.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Additionally, Oliscovicz et al (2015) showed that 65.8% of the HIV-positive children that were included in the study had already developed AIDS.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…El análisis de asociación no mostró diferencias significativas entre las especies aisladas y los factores estudiados (p > 0,05), edad, género, estado inmunológico, manifestaciones orales, estadio clínico o terapia ARV 22,23 . Cabe señalar que todos los varones de esta población tuvieron especies colonizantes (p = 0,007), mientras que la probabilidad de tener un caso de candidiasis fue más alta en las mujeres (OR: 17,27; IC 95% 1,81-+Inf).…”
Section: Artículo Originalunclassified
“…VIH / SIDA años o menos con terapia ARV y se encontraban bajo un esquema TARAA de primera línea. El tiempo de terapia es un factor que influye en las manifestaciones orales de sujetos con TARAA, en específico cuando el esquema incluye a un INNTR 22 . En los resultados de este estudio se observó una alta posibilidad de tener manifestaciones orales en esquemas de primera línea con INNTR (OR: 23,56; IC 95% 2,35-1.259,19), aunque en tratamientos de primera línea con IP se observó un efecto protector (OR: 0,14; IC 95% 0,01-0,94) 4 .…”
Section: Artículo Originalunclassified
“…Among the 4,057 individuals, 468 (11.53%) did not receive HAART or ART. The data from 11 articles (28,33,43,44,48,49,(51)(52)(53)(54)56) demonstrated that HAART or ART were significantly associated with reduction in oral Candida colonization or infection, while others showed the opposite relationship (12,16,32,34,41,42,55), or did not report any statistical data (11, 14, 26, 35-40, 47, 50).…”
Section: Resultsmentioning
confidence: 99%